Gas engineering. Vol. 2, - Speight, James G. (De Gruyter, 2022)
Volume 2 covers the constituents of gas streams and their properties. The author presents the chemistry and engineering aspects of the methods and principles by which the gas streams might be cleaned from their noxious constituents. The concept of gas condensate is also discussed as well as the methods which can be applied to the analysis of streams and condensate. Vol. 1: Origin and Reservoir Engineering. Vol. 3: Uses of Gas and Effects.
Keywords: Gas engineering.; elektronické knihy; electronic books